Digital Based Learning Media Innovation in the Development of Character Education in Senior High School: Inovasi Media Pembelajaran Berbasis Digital Dalam Pengembangan Pendidikan Karakter di Madrasah Aliyah - Rusydiyah, Evi Fatimatur; Mumtahanah, Nurotun; Hamzah, Fachrizal (Universitas Muhammadiyah Sidoarjo, 2021)
In the era of digital learning, educational institutions must innovate to meet the changing needs of the times. The efforts of educational institutions to make their creations and inno- vations a challenge. The innovation carried out by educational institutions aim to equip student competencies according to their time. The purpose of this study is to analyze the innovation of digital-based learning media in the development of character education in MAN I Lamongan. This research method uses case studies with an interview, obser- vation, and documentation data collection techniques. While the data analysis uses the theory of Miles and Huberman, which begins with reducing data, presenting data, and drawing conclusions. The results indicated that 1) MAN 1 Lamongan encourage the inoo- vation through implementation Vision-mission; 2) learning process using positive internet using varied learning media in the form of slides , dynamic visuals that are projected, printed, games, and reality media, and 3) programs of activities including Adiwiyata school programs, ISO programs, D1 equivalent production programs in collaboration with ITS, and Ma'had for sons and daughters. All services connected with Information Technology.